Biaxial fatigue crack propagation behavior of ultrahigh molecular weight polyethylene reinforced by carbon nanofibers and hydroxyapatite. Issue 4 (21st October 2019) - Liu, Zhenduo; Wang, Jianhai; Gao, Hong; Gao, Lilan
Abstract: Ultrahigh molecular weight polyethylene (UHMWPE) artificial joint has remained the preferred polymer component in total joint replacement surgery. However, more and more concerns have been raised about the failure of UHMWPE components due to the initiation and propagation of cracks at the notches with fixed functions. For this reason, biaxial fatigue crack growth (FCG) experiments of UHMWPE reinforced by carbon nanofibers (CNF) and hydroxyapatite (HA) were carried out using elastic–plastic fracture mechanics theory. The FCG resistance of UHMWPE, UHMWPE/CNF, and UHMWPE/HA was compared, and the effects of stress ratio ( R ) value and phase difference on FCG rate were investigated. At the same time, the influence of loading path was considered, and the corresponding crack path was analyzed. Results suggest that UHMWPE/CNF has better FCG resistance and the FCG rate increases with the increase of R value and the existence of 180° phase difference. In addition, crack bifurcation behavior is not observed under nonproportional loading conditions. The findings in this study will provide experimental validation and data support for better clinical application of UHMWPE‐modified materials.